Os itinerários formativos no ensino médio brasileiro instituídos pela Lei nº 13.415/2017: reflexões sobre a formação humana - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This research, entitled The Formative Itineraries in Brazilian High School Education Established by Law No. 13,415/2017: Reflections on Human Formation, was developed in the Research Line State and Educational Policies, of the Graduate Program in Education (PPGE), of the State University of Goiás - Inhumas. The study discusses the High School Reform, having as its analytical focus the investigation of the formative itineraries that make up the proposal of said policy. This study seeks to answer the following question: What conceptions of the term formative itinerary are present in Brazilian educational policy and secondary curricula composed of such orientation materialized in the scope of Brazilian high school education since the implementation of Law No. 13,415/2017? The objectives of this research seek to: historicize the concepts attributed by public policies to the term formative itinerary since the implementation of the high school reform; Identify the media promises aimed at reforming secondary education, as well as the challenges and ideological disputes that permeate traditional and professional education; conduct a bibliographic review of studies that deal with formative itineraries, based on research dedicated to studying the implementation of said reform. The research, of a qualitative nature, was conducted using the content analysis method proposed by Bardin (1977). Based on documentary and bibliographic research, the analysis included authors who researched secondary education reform, specifically the implementation of formative itineraries and their implications for the last stage of basic education. In the documentary research, the following were considered: the Federal Constitution (1988) and current laws governing secondary education: Law No. 9,394/1996, Law No. 10,172/2001, Decree No. 5,154/2004, Law No. 11,741/2008, CNE/CEB Resolution No. 6/2012, Provisional Measure No. 746/2016, Law No. 13,415/2017, Ordinance No. 649/2018, Ordinance No. 1,024/2018, Resolution No. 21/2018, Ordinance No. 1,432/2018, Ordinance No. 733/2021, Ordinance No. 2,092/2023, Law No. 14,945/2024, CNE/CEB Resolution No. 2, of November 13, 2024, among others. The results indicated that the high school reform widened and accentuated inequalities, evidencing characteristics of neoliberal inspiration, aligned with market demands. In this context, the implementation of the most recent high school reform for individuals living in different social, financial and cultural realities proved to be ineffective in promoting equity, as provided for in the Law of Guidelines and Bases of Education (LDB 1996) and in the National Curricular Guidelines for Basic Education (DCNE 2010). Furthermore, the educational itineraries did not guarantee the same opportunities for choice, nor did they ensure educational quality for the comprehensive education of young Brazilians.
The formative itineraries in brazilian secondary education established by law No. 13,415/2017: reflections on human formation
Keywords: Políticas educacionais; Reforma do ensino médio; Formação integral; Currículo escolar; School curriculum; Educational Policies; High School Reform; Comprehensive Education; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::CURRICULO